EDUKASI “SADARI” (PERIKSA PAYUDARA SENDIRI) UNTUK DETEKSI DINI KANKER PAYUDARA DI KELURAHAN CIPAYUNG KOTA DEPOK - Rafiah Maharani PULUNGAN; Fathinah Ranggauni HARDY (Pusat Pengabdian kepada Masyarakat- LPPM Universitas Terbuka, 2020)
The problem of breast cancer and the impact it has created will require public health interventions in the form of a national countermeasure program regulated in Permenkes No. 34 of 2015 concerning Management of Breast Cancer and Cervical Cancer. One of the prevention of breast cancer is case finding with early detection which is done through Breast Self-Examination (BSE) which can be done easily which aims to determine the presence or absence of a lump that can develop into breast cancer. One of the prevention of breast cancer is case finding with early detection which is done through Breast Self-Examination (BSE) which can be done easily which aims to determine the presence or absence of a lump that can develop into breast cancer. The purpose of this activity is to increase knowledge, and change behavior about early detection of breast cancer through Breast Self-Examination (BSE) in Cipayung Village, Depok City. The target audience for this service is the Health Officers and Cadres in the Puskesmas, and especially the mothers in Cipayung Village. The method of implementation of this community service includes the preparation, implementation and evaluation stages. In the preparation stage it was shown that all participants had never received education about BSE before, even 95% of the 32 participants had just heard about BSE. Low initial knowledge can be seen from the results of pre-tests conducted in which the majority of mothers' level of knowledge is still low about breast self-examination and breast cancer after education and training there is an increase in maternal knowledge about breast self-examination. It is recommended that health workers regularly provide education about breast self-awareness to women, especially mothers.